Analisis Kinerja Keuangan PT Bank Central Asia Tbk (BCA) Tahun 2024 Berdasarkan Rasio Profitabilitas, Kualitas Aset, dan Efisiensi Teknologi Informasi - Yuli Kurnia Firdausia; Rohma Desi Ulfinda Sari; Dwi Julia Stifani; Ratih Purwati Ningsih (Jurnal Kajian dan Penelitian Umum, 2025)
This study analyzes the financial performance of PT Bank Central Asia Tbk (BCA) in 2024 through an examination of profitability ratios, asset quality, and efficiency in technological investment. Using a descriptive quantitative approach with secondary data derived from BCA’s official financial reports, the study reveals that BCA achieved a net profit of Rp54.83 trillion, representing 12.74% growth year-on-year, supported by strong operational efficiency and optimal fund management through CASA (Current Account and Savings Account). The Non-Performing Loan (NPL) ratio of 1.8% and Loan at Risk (LAR) of 5.3% demonstrate sound credit quality and effective risk management. Furthermore, the bank’s capital expenditure of Rp4.3 trillion in 2024, focused on digital infrastructure and cybersecurity, enhanced both operational resilience and customer trust. Overall, the findings show that BCA’s success in 2024 was driven by the synergy between financial prudence, technological innovation, and strategic efficiency in responding to the evolving dynamics of Indonesia’s conventional banking sector. This research provides important insights into how BCA manages challenges and opportunities in an increasingly competitive banking industry.